2018
DOI: 10.1155/2018/9738265
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Rupture Caused by Accidental Intubation of the Ureter with a Foley-Catheter during Ureterorenoscopy

Abstract: We would like to present the case of a 64-year-old woman who underwent ureterorenoscopy and suffered an iatrogenic ureteral lesion due to an accidental intubation of the left ureter with a Foley-Catheter during the procedure. A Double-J-Stent was implanted into the damaged ureter, and 6 weeks later it fully recovered. To our knowledge there are few similar cases described in the literature with none of those having happened during ureterorenoscopy so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…These conditions may explain the intraureteral entry of BIC or SPC during their placement or the spontaneous intraureteral migration of the catheter, which can occur on more than one occasion in the same patient (19,27); six reported cases attended the ER between 10 and 60 days after the last catheter replacement. However, this event can also occur in patients with unknown neurological or urological pathology, and two incidental findings have been reported during laparotomy and two cases in the perioperative period of cesarean section (6,12,16,17,23,26,30). The most frequent clinical presentation was a pain in 65% of cases, although this may be absent, especially in patients with upper motor neuron disease due to impaired pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions may explain the intraureteral entry of BIC or SPC during their placement or the spontaneous intraureteral migration of the catheter, which can occur on more than one occasion in the same patient (19,27); six reported cases attended the ER between 10 and 60 days after the last catheter replacement. However, this event can also occur in patients with unknown neurological or urological pathology, and two incidental findings have been reported during laparotomy and two cases in the perioperative period of cesarean section (6,12,16,17,23,26,30). The most frequent clinical presentation was a pain in 65% of cases, although this may be absent, especially in patients with upper motor neuron disease due to impaired pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…fistula. Since it extends from the kidney to the bladder, it reduces the risk of both kidney ectasia and renal failure 4 Kidney stones, ureteral and bladder cancers, ureteral obstructions, ureteral polyps and blood clots are intrinsic reasons for catheterisation. Retroperitoneal fibrosis, maternal hydronephrosis in pregnancy, abscesses, hematomas, vascular anomalies and iatrogenic injuries are extrinsic reasons for catheterisation.…”
Section: Discussionmentioning
confidence: 99%
“…The patients' mean IIEF-15 score and sub-dimension scores a month after double-J catheterisation were lower than their mean scores before catheterisation at significant levels (Table 3). Although the most common purpose of double-J catheterisation is to remove obstruction caused by ureter stones, it is also commonly used to prevent urinary extravasation after surgical operations 3,4 Although double-J insertion has benefits, it also has undesired adverse effects and complications. 7 Previous studies have found that lower urinary tract symptoms emerge after catheter replacement, which causes psychological problems, such as anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review and case series by Luo et al 1 identified 23 cases of ureteric misplacement of catheters and our own review notes eight further cases since. 28 These can present as catheter-related problems such as pain, blockage or bypassing but also with systemic upset including sepsis and acute renal failure. Iatrogenic injuries of the ureter have been reported requiring stenting or surgical repair.…”
Section: Introductionmentioning
confidence: 99%
“…Iatrogenic injuries of the ureter have been reported requiring stenting or surgical repair. 8,9 Ureteric catheterisation has also been noted to occur in suprapubic catheters and as result of diagnostic imaging. 7,10…”
Section: Introductionmentioning
confidence: 99%